Man and Nature: An Eco-critical Study of Ian McEwan's Atonement - Nseif, Zeena Alwan (Al-Adab Journal, 2019)
Recently, eco-criticism attracted the attention of many writers. Ian McEwan is one of the brilliant novelists who is interested in ecology mainly because he thinks that the world is swept by technology and consequently man is drifted away from nature. Therefore, Atonement (2001) is a call to go back to nature because it is part and parcel of man's life. . Natural environment is the source of purity and inspiration and it has its effect on man's life.This research is an eco-critical study of Ian McEwan's Atonement, one of his early novels which celebrates the symbiotic relationship between man and nature and nature and culture.